Resepsi Ayat-Ayat Al-Qur’an Terhadap Seni Kaligrafi Di Mushola Al-Muttaqin, Kampung Cidunak, Kota Cilegon - Karim, Sultan; Lubis, Ahmad Anshori; Kurniawan, Ade Fakih (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2023)
Calligraphy is one of the expressions of Islam that has received tremendous attention from Muslims. In essence, calligraphy is a work of beautiful composition (khat) taken from the Qur'an and named (where it appears) Makki, Madani, Anbari, and Baghdadi. In the long run, several names (khat) emerged, such as khat Khufi, mutsallat, mudawwar, and others. The impact of the expansion of Islamic rule, the expansion of Bedouin rule, the duties of rulers, and the world class society inspired and worked with the increase of calligraphic specificity and influenced the logical turn of events, especially during the Abbasid period. After the Abbasid period, calligraphy really existed and was created. The purpose of this article is to understand how Quranic verses are understood and applied in the field of calligraphy, as well as how the craft of calligraphy is acquired by people who visit the demand room. Exploratory strategies used may include perception, encounter, and text examination. The results of the examination may provide a better understanding of the relationship between the verses of the Quran and the specialty of calligraphy, as well as provide data on how the craft of calligraphy is perceived by individuals who visit the request room.